IT Governance Design in XY University using Cobit 2019 Framework - Mangoki, Willson; Manongga, Danny; Iriani, Ade (Jurnal Sistem Informasi Bisnis, 2024)
The management and control of information and technology at the university were required for IT's finest use, but in line with organization goals, they can be realized with the use of IT governance. This research uses a qualitative approach with techniques such as interviews, observation, expert judgment, and literature studies that are relevant to the concept of IT governance with the COBIT framework and its application in various fields. This research presents an IT governance design that is considered suitable to be applied at XY University using COBIT 2019 Framework. 10 design factors and 40 IT processes listed in COBIT 2019 are used as parameters. The results obtained from four processes with scores ranging from 50 to 100 with capability levels 3 and 4, namely APO04-Managed Innovation, APO03-Managed Enterprise Architecture, APO07-Managed Human Resources, and BAI07-Managed IT Change Acceptance and Transitioning, are translated into recommendations for actions that need to be taken in implementing IT governance.